PEMAKNAAN KHALAYAK TENTANG MEDIA ONLINE INSTAGRAM - Mandemasya, Herna (Universitas Prof. Dr. Moestopo (Beragama), 2015)
The purpose of this study was to determine the meaning of online media audiences about Instagram. The role of mass media communication technologies increasingly rapid developmentan dplays an important rol efor people ine veryday life. Internet is very helpful in the field of marketing (online marketers).One growing form of online promotion today is through instagram, is based photo sharing append customarily found on a smartphone. As a start-up business enterprise cause the instagram application, because through the internet phenomenon popping up lately many new products are marketed. To that end, inthis paper, how the instagram app-based photo sharing can be defined, especially for people who responded to the promotion of start-ups bussines.